Temporary Work in Turbulent Times: The Swedish Experience - Bertil Holmlund; Donald Storrie (Center for Economic Studies and ifo Institute (CESifo), 2002)
Sweden has experienced a substantial increase in temporary work over the 1990s, with most of the rise occurring during a severe macroeconomic recession with mass unemployment. By the early 1990s, workers on fixed-term contracts accounted for 10 percent of the number of employees; by the end of the decade they accounted for 16 percent. The paper presents the Swedish institutional setting, documents basic stylised facts about fixed-term contracts, and discusses the causes of their increased prevalence. Our analysis reveals that open-ended and temporary employment exhibit strikingly different cyclical behaviour with temporary employment being more volatile. A recession is associated with an initial decline in temporary employment followed by a sharp rise from the trough to the end of the recession. We argue that the severe recession of the 1990s is a major factor behind the rise in temporary work in Sweden. Adverse macroeconomic conditions make firms more prone to offer fixed-term contracts and workers more willing to accept them.
Keywords: 330; temporary jobs; labour market dynamics; unemployment